Populism and affective polarization in the times of 'Giorgia': an assessment of the effect on European voting - Antonino Castaldo; Danilo Di Mauro; Vincenzo Memoli (QOE-IJES, 2025)
Despite the attention paid by comparative studies to the themes of populism and affective polarization (AP), the connections between these two concepts remain under-investigated. Both of them describe the conflict between ingroup (“us”) and outgroup (“them”) individuals. Nonetheless, although in the first case, the conflict pits the people against the elite, in the second case conflict occurs between party supporters and other parties (e.g., leaders, members). Even if conceptually and empirically separate, populism and AP are key explanatory factors of today’s politics and voting behavior. The increase in voter discontent, also fueled by a succession of economic, migratory, and pandemic crises, has indeed facilitated the rise of populists and affective sentiments. Do they work in parallel or show some points of contact? How do they interact in voting choices across different parties?